Gerakan Penguatan Sadar Sampah: Pelatihan Pemilahan Sampah untuk Membangun Generasi Peduli Lingkungan di Sekolah Dasar - Septiani, Riana; Sundari, Susanti; Pratiwi, Mirandhi; Suharto, Suharto; Gustaf, Alitna Liberty (Lembaga penelitian dan pengabdian kepada masyrakat, 2025)
The community service activity at SDN 1 Bumi Waras, located in a densely populated village and a center for kemplang cracker production near the coast, aimed to address the low level of public environmental awareness regarding cleanliness. Utilizing the Participatory Action Research (PAR) method, which involved a collaborative effort between lecturers and students from the Industrial Engineering program at Universitas Tulang Bawang and PT. BMI Lampung, the program focused on empowering elementary school students to foster an environmentally conscious and waste-caring culture from an early age. The results of the socialization and simulation demonstrated a significant increase in students' understanding of waste sorting, from 10% to 95%, affirming the activity's success in instilling environmental awareness for sustainability.